2018
DOI: 10.1371/journal.pone.0207908
|View full text |Cite
|
Sign up to set email alerts
|

PCSeg: Color model driven probabilistic multiphase level set based tool for plasma cell segmentation in multiple myeloma

Abstract: Plasma cell segmentation is the first stage of a computer assisted automated diagnostic tool for multiple myeloma (MM). Owing to large variability in biological cell types, a method for one cell type cannot be applied directly on the other cell types. In this paper, we present PCSeg Tool for plasma cell segmentation from microscopic medical images. These images were captured from bone marrow aspirate slides of patients with MM. PCSeg has a robust pipeline consisting of a pre-processing step, the proposed modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…However, in the long-term follow-up, there was no significant difference in the mortality rate between the two types of stents [ 21 ]. Duggalb et al, reported that there was a statistically significant difference in unadjusted mortality rates between the BMS (5%) and DES (3.8%) [ 26 ]. Also, in the study by Dieguez et al [ 27 ], the rate of all-cause mortality in patients treated with DES (6.5%) was significantly lower than that of patients treated with BMS (12.2%) ( P = 0.049).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the long-term follow-up, there was no significant difference in the mortality rate between the two types of stents [ 21 ]. Duggalb et al, reported that there was a statistically significant difference in unadjusted mortality rates between the BMS (5%) and DES (3.8%) [ 26 ]. Also, in the study by Dieguez et al [ 27 ], the rate of all-cause mortality in patients treated with DES (6.5%) was significantly lower than that of patients treated with BMS (12.2%) ( P = 0.049).…”
Section: Discussionmentioning
confidence: 99%
“…The microscopic images of multiple myeloma cells applied in this research were obtained from the TCIA_SegPC_dataset [ 4 , 9 , 10 ]. It is a publicly released dataset for academic and research purposes after the SegPC2021 challenge.…”
Section: Methodsmentioning
confidence: 99%
“…We try to remove unstained cells because they can hinder the learning process of Mask R-CNN. A study by Gupta [ 4 ] performed a detailed analysis of different objects from the input cells images. They emphasized four different objects (ROIs): the nucleus of plasma cells, cytoplasm of plasma cells, unstained cells, and background.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm developed is based on Otsu's thresholding. Gupta [15] in his research, he presented the PCSeg Tool for segmenting blood plasma cell images. The algorithm that he uses is pre-processing the existing input images by removing all information that is not needed so that all that remains is the region that does provide information about the blood plasma cells only.…”
mentioning
confidence: 99%